Vaccination with an alkaline extract of Histoplasma capsulatum packaged in glucan particles confers protective immunity in mice. Issue 23 (31st May 2018) - Deepe, George S.; Buesing, William R.; Ostroff, Gary R.; Abraham, Ambily; Specht, Charles A.; Huang, Haibin; Levitz, Stuart M.
Highlights: An alkaline extract from Histoplasma capsulatum packaged in glucan particles vaccinates mice. This vaccine induces a vigorous Th1 and Th17 response in lungs and lymphoid tissue. Tc17 cells were modestly induced in lungs. The vaccine provokes production of both IL-17 and IFN-γ. IL-17 and IFN-γ are independently required for protection. Abstract: Infection with the dimorphic fungus, Histoplasma capsulatum, occurs world-wide, but North and South America are regions of high endemicity. Interventions to mitigate exposure and consequent disease are limited to remediating a habitat harboring the fungus. The development of a vaccine to prevent infection or lessen its severity is an important advance in disease prevention. Accordingly, we prepared an alkaline extract from the yeast phase of Histoplasma and encased it in glucan particles that act as an adjuvant and delivery vehicle. Immunization of C57BL/6 mice with this encapsulated extract decreased the number of CFUs in lungs and spleens at days 7 and 14 following intranasal infection. Moreover, this vaccine conferred protection against a lethal challenge with the fungus. Cytokine assessment in lungs at a time when the CFUs were similar between controls and vaccinated groups revealed increased quantities of interferon-γ and interleukin-17 in vaccine recipients. This finding was supported by increased generation of both Th1 and Th17 cells in lungs and draining lymph nodes of vaccinated mice compared to controls. Neutralization of interferon-γ or interleukin-17 blunted the effectiveness of vaccination. To identify the proteins comprising this extract, liquid chromatography tandem mass spectrometry was performed. Thus, an H. capsulatum alkaline extract packaged in glucan particles confers protection in an interferon-γ and interleukin-17-dependent manner. Discovery of a single protein or a few proteins in this admixture that mediate protective immunity would represent significant progress in efforts to prevent histoplasmosis.